2016
DOI: 10.1089/neu.2015.3945
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Docosahexaenoic Acid Improves Cognitive Function, Tissue Sparing, and Magnetic Resonance Imaging Indices of Edema and White Matter Injury in the Immature Rat after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is the leading cause of acquired neurologic disability in children. Specific therapies to treat acute TBI are lacking. Cognitive impairment from TBI may be blunted by decreasing inflammation and oxidative damage after injury. Docosahexaenoic acid (DHA) decreases cognitive impairment, oxidative stress, and white matter injury in adult rats after TBI. Effects of DHA on cognitive outcome, oxidative stress, and white matter injury in the developing rat after experimental TBI are unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 88 publications
2
41
1
Order By: Relevance
“…45 Though a mouse model of frontal lobe CCI injury to a toddler-age equivalent (P21) has shown a chronic motor deficit, 17 no other preclinical models of infant or toddler TBI have shown chronic motor deficits following early CCI. 1,84,106 Thus, even though the deficits detected in the present study were subtle, this is the first time that chronic significant gait differences in infant CCI-veh rats were identified. Most importantly, EPO treatment reversed the motor deficits.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…45 Though a mouse model of frontal lobe CCI injury to a toddler-age equivalent (P21) has shown a chronic motor deficit, 17 no other preclinical models of infant or toddler TBI have shown chronic motor deficits following early CCI. 1,84,106 Thus, even though the deficits detected in the present study were subtle, this is the first time that chronic significant gait differences in infant CCI-veh rats were identified. Most importantly, EPO treatment reversed the motor deficits.…”
Section: Discussionmentioning
confidence: 44%
“…In a preclinical model of toddler TBI with P17 CCI, a reduction in white matter RD related to an oral treatment regimen was observed. 84 Indeed, detailed imaging studies have demonstrated differences in treatment groups when preterm infants were imaged at a term-equivalent age, 5,46 a relatively short interval of a few months to detect structural improvement in neurodevelopment in humans. These recent reports, 5,46 in combination with data presented here, suggest that DTI may be used as an imaging biomarker in infant TBI to measure responsiveness to neuro-reparative strategies.…”
Section: Discussionmentioning
confidence: 99%
“…An ex vivo study found that RD was elevated in demyelinating spinal cord tissue from multiple sclerosis patients [55]. It is also notable that DHA blunted elevated RD in the neonatal rat brain following controlled cortical impact [56]. However, an ex vivo study found that RD was significantly correlated with MBP immunolabeling only in commissural WM tracts [57].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is intriguing, as it would allow us to further understand the impact of immune factors on brain structure. Moreover, there is evidence that omega-3 fatty acids have anti-inflammatory effects (140, 141). Thus, in addition to the previously discussed role for PUFA supplementation in supporting myelination, it is also possible that the preventative effects are related to inflammation.…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%